MEMPERKUAT KESADARAN BELA NEGARA GENERASI MILENIAL MELALUI MANAJEMEN PERTAHANAN TERHADAP ANCAMAN EKONOMI PASCA PANDEMI COVID-19 - Nafita Azkiya; Jonni Mahroza; Agung Risdhianto; Hikmat Zakky Almubaroq (CV. AFDIFAL MAJU BERKAH, 2023)
The Covid-19 pandemic that hit globally at the end of 2019 had a significant impact on the Indonesian economy. The PSBB (Large-Scale Social Restrictions) policy enacted at that time caused various economic problems such as increasing commodity prices in the market and increasing unemployment due to layoffs (Termination of Employment) which occurred due to the declining economic growth rate. This research uses a qualitative approach that aims to identify how the economic impact of the post-Covid-19 pandemic in Indonesia and outline how appropriate state defense efforts for the millennial generation to face economic threats as non-military threats that affect national resilience. The results of this study confirm that the concept of state defense efforts must be implemented gradually and continuously in order to instill awareness of state defense in the younger generation. This approach can be done through various channels, both through formal and non-formal education. Promoting the concept of universal defense by involving all potential national resources is key in strengthening national character building. This is done by fostering awareness and state defense skills for every Indonesian citizen, so that they are ready to become part of the human resources that defend the country. Moreover, this approach also strengthens national identity that is rooted in personality and culture based on the values of Pancasila. Given the impact of the Covid-19 pandemic on Indonesia's economy, including rising prices of basic necessities, high unemployment rates, and declining investment, it is important that we raise state defense awareness and educate Millennials about their role in maintaining the country's resilience.